Cross-paradigms or the interfaces of word-formation patterns: evidence from Portuguese - Rodrigues, Alexandra Soares (2019)
A paradigmatic approach has been applied to derivational morphology in recent studies (Štekauer 2014; Antoniová & Štekauer 2015; Blevins 2016). One of those studies (Rodrigues 2016) proposes the notion of cross-paradigms to describe the intersection of process-organised with affix-organised paradigms. This paper brings psycholinguistic evidence to the mental status of cross-paradigms, based on experimental data obtained from native Portuguese speakers. Cross-paradigms reveal the dynamic nature of the mental lexicon, as Elman (2011) and Libben (2014; 2015) have claimed.